PHẢN ỨNG GHÉP GLYCIDYLMETACRYLAT LÊN POLYETYLEN PHẦN I. ẢNH HƯỞNG CỦA CÁC YẾU TỐ CÔNG NGHỆ ĐẾN PHẢN ỨNG GHÉP - Thuỷ, Nguyễn Thị; Tùng, Nguyễn Huy; Chương, Bùi (Vietnam Journal of Chemistry, 2012)
Grafting reactions of glycidylmethacrylate on polyethylene were carried out in a Brabender internal mixer with capacity of 50 ml. There are strong and sharp peak in the PE-g-GMA IR spectra at about 1730 cm-1 corresponding to carbonyl group (C=O) and at 850 và 910 cm-1 corresponding epoxy group, but these peaks have not seen in neat PE spectra. The parameters of process condition were selected to achieve the highest grafting content: the temperature at 185oC, rotor speed of 40 rpm for 11 min. The received PE-g-GMA possessed: grafting content 1.705 wt.%, melt flow index 5.27 g/10 min and contact angle 45.21o.